Widening the infantile hypotonia with psychomotor retardation and characteristic Facies-1 Syndrome’s clinical and molecular spectrum through NALCN in-silico structural analysis - Vecchio, Davide; Macchiaiolo, Marina; Gonfiantini, Michaela V.; Panfili, Filippo M.; Petrizzelli, Francesco; Liorni, Niccolò; Cortellessa, Fabiana; Sinibaldi, Lorenzo; Rana, Ippolita; Agolini, Emanuele; Cocciadiferro, Dario; Colantoni, Nicole; et al. (Frontiers in Genetics, 2024)
IntroductionInfantile hypotonia with psychomotor retardation and characteristic facies-1 (IHPRF1, MIM#615419) is a rare, birth onset, autosomal recessive disorder caused by homozygous or compound heterozygous truncating variants in NALCN gene (MIM#611549) resulting in a loss-of-function effect.MethodsWe enrolled a new IHPRF1 patients’ cohort in the framework of an international multicentric collaboration study. Using specialized in silico pathogenicity predictors and ad hoc structural analyses, we assessed the mechanistic consequences of the deleterious variants retrieved on NALCN structure and function.ResultsTo date 38 different NALCN variants have been retrieved from 33 different families, 26 from unrelated and 22 from related patients. We report on five new IHPRF1 patients from four different families, harboring four newly identified and one previously retrieved variant that exhibited a markedly significant functional impact, thereby compromising the functionality of the protein complex.DiscussionBy widening the functional spectrum of biallelic variants affecting the NALCN gene, this article broadens the IHPRF1 syndrome’s genotype-phenotype correlation and gives new insight into its pathogenic mechanism, diagnosis, and clinical management.